Mild and moderate Mannose Binding Lectin deficiency are associated with systemic lupus erythematosus and lupus nephritis in Brazilian patients - Sandro Félix Perazzio (Revista Brasileira de Reumatologia, 2016)
Abstract Objective The potential association of mannose binding lectin (MBL) deficiency and systemic lupus erythematosus (SLE) has been investigated in several studies, but results have been mixed. One explanation for the conflicting results could be differences in ethnic background of study subjects. In this study we investigated the association of MBL deficiency and SLE in a large cohort of Brazilian SLE patients and controls. Methods Serum MBL and Complement levels were determined for 286 Brazilian adult SLE patients and 301 healthy Brazilian adults as controls. MBL deficiency was classified as mild (<1000 and ≥500 µg/L), moderate (<500 and ≥100 µg/L) or severe (<100 µg/L). Results SLE patients presented higher frequency of mild and moderate MBL deficiency compared to controls. SLE patients with MBL deficiency presented higher frequency of lupus nephritis compared to those without MBL deficiency. MBL deficiency was not associated with any other clinical manifestation, use of immunosuppressant therapy, disease activity, disease severity serum or Complement levels. Conclusion This study shows that an association between MBL deficiency and SLE does exist in the Brazilian population. We also found an association between MBL deficiency and lupus nephritis. These findings support the hypothesis that MBL deficiency contributes to the development of SLE and lupus nephritis.